Reliability and validity of the East Asian children's version of mini-MACS in children with cerebral palsy - Hou, Xiaohui; Qiu, Huiying; Liu, Liru; Li, Yinhua; He, Lu; Li, Jinling; Tang, Hongmei; Xu, Kaishou (Frontiers in Rehabilitation Sciences, 2022)
Background Mini-Manual Ability Classification System (Mini-MACS) was developed for children with cerebral palsy aged 1–4 years, but its validity and reliability in different cultures are unavailable yet. This study was to determine the reliability and validity of Mini-MACS in East Asian children with cerebral palsy and investigate the correlation between Mini-MACS and Gross Motor Function Classification System. Methods One hundred and four East Asian children with cerebral palsy aged 12–48 months were classiﬁed by one of their parents, an occupational therapist, and a physical therapist with Mini-MACS. The results were analyzed for inter-rater reliability by using intraclass correlation coefficient (ICC). The Nine-hole Peg Test was used for the criterion-related validity analysis, and parents retested their children after 2 weeks to evaluate test–retest reliability. Gross Motor Function Classification System levels were also collected to investigate the correlation with Mini-MACS. Results Good inter-rater reliability among the occupational therapist, physical therapist, and parents was found [ICC = 0.984 (95% confidence interval, CI, 0.976–0.989), 0.973 (95% CI 0.960–0.982), and 0.966 (95% CI 0.950–0.977), respectively; p < 0.01]. The test–retest reliability in parents was almost perfect [ICC = 0.985 (95% CI 0.977–0.990), p < 0.01]. Mini-MACS had consistency with the Nine-hole Peg Test (r = 0.582, 0.581, and 0.566, respectively; p < 0.01). A correlation was found between Gross Motor Function Classification System and Mini-MACS (r = 0.626, 0.596, and 0.598, respectively; p < 0.01). Conclusion The Mini-MACS demonstrates evidence that it is a valid and reliable tool to classify manual ability in East Asian children with cerebral palsy and is also positively related to the Gross Motor Function Classification System.